Marketing that works how entrepreneurial marketing can add sustainable value to any sized company - Lodish, Leonard M. (Wharton School Pub., 2007)
"Marketing That Works introduces breakthrough marketing tools, tactics, and strategies for differentiating yourself around key competencies, insulating against competitive pressures, and driving higher, more sustainable profits." "From pricing to PR, advertising to viral marketing, this book's techniques are relentlessly entrepreneurial: designed to deliver results fast, with limited financial resources and staff support. They draw on the authors' decades of research and consulting, their cutting-edge work in Wharton's legendary Entrepreneurial Marketing classes, and their exclusive new survey of the Inc. 500's fastest-growing companies."--Jacket
Includes bibliographical references and index. - Print version record
Keywords: New business enterprises -- Management; Industrial management; Marketing -- Management; Entrepreneurship; Nouvelles entreprises; Gestion; Gestion d'entreprise; Marketing; Gestion; Entrepreneuriat; entrepreneurs; Marketing; Management; New business enterprises; Management